A novel LDMOS with optimized electric field distribution to eliminate substrate assisted depletion effect. (October 2022) - Zhu, Shunwei; Jia, Hujun; Yang, Yintang
Abstract: A novel N -channel Super Junction Lateral double-diffused MOSFET (SJ LDMOS) with optimized electric field distribution is proposed. To eliminate substrate assisted depletion (SAD) effect, the source-drain electrodes of the proposed device are used to form a voltage in the substrate equal to the SJ layer. Then the surface of the substrate is depleted through the buffer layer. The substrate and the SJ layer are independently depleted, and form a similar electric field distribution. The influence of the substrate on the SJ layer is greatly removed. Finally, the influence of the substrate on SJ layer is completely eliminated. Under the same drift length of 20 μm, the specific on resistance ( R on, sp ) and breakdown voltage ( BV ) of the proposed SJ LDMOS are reduced by 60.09% and 28.9% compared with those of the conventional SJ LDMOS, respectively. With the increase of the drift region length, the SJ LDMOS which eliminates the SAD effect has more obvious advantages in the high voltage field.